Mechanical behaviour of 2D hybrid structure fabricated by doping graphene with triangular h-BN cells. (July 2021) - Jia, Ziqian; Wang, Guotong; Wang, Liya; Tang, Chun; Wang, Chengyuan
Abstract: A two dimensional (2D) hybrid structure has been fabricated by doping graphene with hexagonal boron nitride (h-BN) cells. Substantial changes are expected as carbon-carbon (C) bonds are substituted by B–N bonds and C–B and C–N bonds are formed between the BN cells and graphene. In this paper, molecular dynamics simulations are performed to explore the tensile behaviour and fracture mechanisms of the 2D HS, and reveal how and to what extent the BN cells impact its overall tensile properties. A comprehensive study of free boundary effects is also conducted for the first time for 2D materials. Herein, the 2D nonlinear elastic constitutive relation has been formulated in terms of the equivalent elastic modulus Y e that decreases almost linearly with BN content α due to the distinct elastic properties between B–N bonds and C–C bonds. The downward trend of the fracture stress with growing α is also achieved due to the α − dependence of Y e and the limit on the fracture strain imposed by the newly formed C–B bonds. In addition, evidence has been accumulated showing that the free boundaries can significantly decrease the elastic moduli and fracture stress but largely enhance the fracture toughness of the 2D nanosheets. Highlights: Formulated the 2D nonlinear constitutive relation for the 2D hybrid structure. Derived the formula for the nonlinear elastic moduli─BN content relationship. Studied the fracture mechanisms and the effect of BN content on the fracture. Disclosed the role of B–N and C–B bonds in shaping the mechanical behaviour. Explored the boundary effects on the mechanics of the 2D hybrid structure. .